2018
DOI: 10.1002/lary.27766
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tranexamic acid on operative bleeding in endoscopic sinus surgery: A meta‐analysis and systematic review

Abstract: Objectives Tranexamic acid might help control bleeding during surgery because of antifibrinolytic characteristics. We aimed to evaluate the effectiveness of systemic tranexamic acid compared to control in blood loss, operative time, and surgical field and incidence of postoperative emesis and thromboembolism in endoscopic sinus surgery. Methods Two authors independently searched six databases (PubMed, SCOPUS, Embase, the Web of Science, Google Scholar, and the Cochrane database) from their inception to July 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 28 publications
2
43
1
1
Order By: Relevance
“…In this study, despite the better surgical visualization in the TXA group, the reduction in blood loss and OT by TXA administration was not significant, which differs from the findings in a previous study ( 5 ). This difference might be related to the severity of the disease.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this study, despite the better surgical visualization in the TXA group, the reduction in blood loss and OT by TXA administration was not significant, which differs from the findings in a previous study ( 5 ). This difference might be related to the severity of the disease.…”
Section: Discussioncontrasting
confidence: 99%
“…A systematic review (6) found that TXA improved the surgical field and reduced blood loss during nasal surgery. The meta-analysis performed by Kim et al ( 5 ) found that TXA reduced blood loss and operative time in endoscopic sinus surgery based on a small number of enrolled studies. Langille et al ( 7 ) applied a bolus TXA of 15 mg/kg with a continuous TXA infusion at 1 mg/kg/h and did not find decreased efficiency in the surgical field or intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we found that the best quality of the surgical field was obtained in patients who received the combined both topical and IV TA (group C), followed by those who received the IV TA (group A), while those who received the topical TA (group B) had the lowest surgical field quality. Various studies have shown that IV administration of TA significantly decreased intraoperative bleeding as compared to control groups, with no detection of significant thrombotic events or alterations in coagulation parameters postoperatively 20,22‐24 . It remains to be mentioned that fentanyl consumption was significantly lower in group C as compared to the other groups, and hence, that led to a significantly shorter recovery time.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to BL during surgery, post-surgery BL is also one of the major complications of thyroidectomy that leads to the patient not being discharged and prolongation of the hospitalization period, the respiratory tract being jeopardized, and even reoperation in some cases. [4,5] Some studies have hitherto been conducted on TA effectiveness in head and neck surgeries, as well as elective and emergency operations, [6,7] but studies dedicated to thyroid surgeries have been very limited. The present study aims to investigate the impact of TA in controlling BL during and after thyroid surgery in Shahid Rahnemoun Hospital in Yazd, Iran during 2018 and 2019.…”
Section: Can Tranexamic Acid Control Bleeding During and After Total Thyroidectomy? A Randomized Double-blind Clinical Trial Studymentioning
confidence: 99%